TOTAL MANAGEMENT IN THE SPHERE OF TOURIST SERVICES - Bikenova, A.S.; Madisheva, A.M.; Nurgabylov, M.N.; Karabayeva, R.K. (Academic Journal of Physical and Chemical Sciences, 2018)
Total management of tourist services, as a rule, is based on the participation of all members of the tourism organization, as it aims to achieve long-term success, bringing benefits to all stakeholders in accordance with international standards. Ensuring the quality of tourist services involves a regular check of the progress in achieving the goals in accordance with certain requirements for quality. The quality of tourist services is assured based on a previously approved quality plan, process maps, checklists and other quality documentation, as well as data on the quality of tourist services obtained as a result of monitoring and testing. In each case, it is necessary to find the optimal combination between the types of control, which depends on the nature of production and the contingent of tourist industry workers. The authors cited the wording of the ISO-9000 family of standards and the provisions of the TQM concept, which have differences.